Use, value, and desire: ecosystem services under agricultural intensification in a changing landscape in West Kalimantan (Indonesia) - Sutherland, I.J.; Van Vianen, J.; Rowland, D.; Palomo, I.; Pascual, U.; Mathys, A.; Narulita, S.; Sunderland, T.C.H. (Springer, 2023)
A fundamental challenge is to understand and navigate trade-offs between ecosystem services (ES) in dynamic landscapes and to account for interactions between local people and broad-scale drivers, such as agricultural intensification. Many analyses of ES trade-offs rely on static mapping and biophysical indicators while disregarding the multiple uses, values, and desires for ES (UVD-ES) that local people associate with their changing landscapes. Here, a participatory UVD-ES framework was applied to assess differences in the use, values, and desire of ES between three zones with different land-use intensities (with pre-frontier, frontier, and post-frontier landscapes) in West Kalimantan (Indonesia). The analysis revealed that (1) almost the full suite of ES uses has become destabilized as a result of agricultural intensification; (2) ES more closely associated with agricultural intensification were largely desired by local people yet they still valued a diversity of traditional ES, such as those derived from the provision of non-timber forest products, fish, and other ES associated with non-material aspects including those tied to traditional culture; (3) the mismatch in used ES versus valued ES increased with agricultural intensification due to a decrease in the flow of non-timber forest products, aquatic, regulating, and non-material (cultural) ES. Together, exploring UVD-ES patterns in a participatory way helped to reveal locally relevant social-ecological drivers of ES and a multidimensional perspective of ES trade-offs. Our UVD-ES framework offers an opportunity to foster participation as a way to reconnect global environmental research agendas with local and regional landscape contexts.